Tests on the effect of shape on the strength of castings - White, Leon Vincent; Corbin, De Verne (My University, 1903)
Introduction: Introduction: It was our intention upon taking up this subject for ta thesis, to deal mainly with beams of various cross-section; to ascertain their transverse strength and the effect of the shape of the sections chosen upon this strength, but owing to unforeseen difficulties which prevented the foundry from maintaining their usual supply of iron, it was impossible to cast the specimens and so we were limited almost entirely to tests in compression and tension, using the common test bars on hand and those specimens that we could turn from them. The first test made was that of finding the relative strength of cast iron, in tension and compression. For this purpose specimens were turned three-fourths of an inch in diameter and one and a half inches long, five specimens being tested in compression and five in tension. The average breaking lad of the specimens tested in tension was 21,852 pounds per square inch, and for those in compression 112,473 pounds per square inch this giving the ratio of the breaking load in tension to the breaking lad in compression as 1 is to 5.147. Results of this test are shown in table number one. The second test (results shown in table number two) was made with turned bars in tension, sixteen specimens being broken in all; six of the shapes shown by figure one, four like figure two, three like figure three and three like figure four. The first specimen was simply a turned bar, the finished surface being of no specified length and the shoulders lift round. In the second a V shaped cut was made in the surface of the bar with a diamond nose lathe tool. The third specimen was treated the same as the second except that in place of the diamond nose a round nose tool was used, cutting a U shaped groove.
Citation: White, Leon Vincent and Corbin, De Verne. Tests on the effect of shape on the strength of castings. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: Castings; Cross-section beams; Compression; Tension; Theses